Ephesians - MCGEE, Vernom, J 1991 (Nashville Thomas Nelson Publishers, 1991)
Radio messages from J. Vernon McGee delighted and enthralled listeners for years with simple, straightforward language and clear understanding of the Scripture. Now enjoy his personable, yet scholarly, style in a 60-volume set of commentaries that takes you from Genesis to Revelation with new understanding and insight. Each volume includes introductory sections, detailed outlines and a thorough, paragraph-by-paragraph discussion of the text. A great choice for pastors - and even better choice for the average Bible reader and student! Very affordable in a size that can go anywhere, it's available as a complete 60-volume series, in Old Testament or New Testament sets, or individually.
contains bibliography
Keywords: ephesians ,bible commentaries